The river you touch : making a life on moving water - Dombrowski, Chris, 1976- (Milkweed Editions, 2022)
"We are matter and long to be received by an Earth that conceived us, which accepts and reconstitutes us, its children, each of us, without exception, every one. The journey is long, and then we start homeward, fathomless as to what home might make of us."--